Pengaruh Curent Ratio, Return On Asset, Debt To Equity Ratio dan Total Asset Turn Over Terhadap Return Saham Perusahaan Perbankan di Bursa Efek Indonesia Tahun 2018-2022 - Mutiara Arsy, Anandhita; Afif, M. Nur; Anwar, Saeful (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to find out how to get the desired stock returns by carrying out your own analysis of stock trading behavior, or by using the tools provided by analysis in the capital market. Information that can be used as a benchmark for the level of stock returns of the companies studied is the current ratio, return on assets, debt to equity ratio and total asset turnover. The population in this study were 13 banking sub-sector companies registered on the IDX in 2018-2022. The analysis used is descriptive analysis, classical assumptions, multiple linear regression analysis and hypothesis testing. The results of this research show that the current ratio has a negative and insignificant effect on stock returns. Return on assets has no and significant effect on stock returns, debt to equity ratio has a positive and not significant effect on stock returns and total asset turnover has a positive and not significant effect on stock returns